Pengaruh Metode Role Play Terhadap Pemahaman Perilaku Perundungan Siswa Kelas V - Ramadani, Suci; Dafit, Febrina (Cetta: Jurnal Ilmu Pendidikan, 2025)
Bullying is a repetitive act intended to harm someone both mentally and physically, and this phenomenon is a serious concern in schools. One effective effort to enhance students' understanding of bullying behavior is through the role-play method. This research aims to analyze the influence of the role-play method on improving students' understanding of bullying behavior. The study employed an experimental method with a one-group pretest-posttest design, involving 29 fifth-grade students from SDN 193 Pekanbaru as the sample. Data were collected using questionnaires and analyzed quantitatively with SPSS version 25 software. The results of the paired t-test showed a significance value of 0.001 (p<0.05). This figure indicates the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1), proving a significant influence of the role-play method in enhancing students' understanding of bullying behavior. This improvement in understanding was evident from consistently higher posttest scores compared to pretest scores. The role-play method proved effective in facilitating students to internalize various perspectives, comprehend the negative impacts of bullying, and develop empathy, thereby making their understanding of this behavior more comprehensive. Thus, this study concludes that the role-play method is highly effective in improving students' understanding of bullying behavior. The implication of these findings is the importance of integrating role-play as an innovative learning strategy into the school curriculum to foster a safer and bullying-free learning environment.